المسؤوليّة التأديبيّة للموثّق وفق القانون 06/02 - بن زموري نو ارلدين (جامعة المسيلة, 2024)
يتحمل الموثّق أثناء ممارسته لمهنته مسؤوليّة أي خطأ مهنيّ يخلّ بواجباته والتزاماته ينجرّ عنه متابعته أمام المجلس التّأديبي، وفق إجراءات نظّمها المشرّع من خلال القانون رقم 06-02 المتضمن تنظيم مهنة الموثق ، بداية من إخطار المجلس التأديبي واستدعاء الموثّق المعني للمثول أمامه مع توفير ضمانات له كحق الدّفاع و الاستعانة بمحام أو ممثل له و كذا اطّلاعه على ملفه التّأديبي، إضافة إلى تمكينه من الطّعن في القرار التّأديبيّ الصّادر في حقه أمام اللّجنة الوطنية للطّعن و الّتي تصدر بدورها قرارا قابلا للطّعن أمام مجلس الدّولة ،حيث يعدّ الطّعن في القرار التّأديبيّ ضمانة هامة لمصلحة الموثّق المتابع تأديبيّا، و بالرّغم من هذه الضّمانات فإنّ عدم حصر الأخطاء المهنيّة و كذا تصنيفها حسب جسامتها وتحديد العقوبات الّتي يستوجبها كلّ خطأ قد يؤثر سلبا على النظام التّأديبي و تحقيقه للأهداف المرجوة منه من حماية للمهنة و المهنيّ. الكلمات المفتاحية: المسؤولية التأديبية، القرار التأديبي، الخطأ التأديبي Abstract During the exercise of his profession, the notary shall bear the responsibility for any professional error that violates his duties and obligations that results in his follow-up before the Disciplinary Council, in accordance with procedures regulated by the legislator through Law No. 06-02 regulating the profession of the notary, starting with notifying the disciplinary council and summoning the concerned notary to appear before it with guarantees such as the right of defense and the assistance of a lawyer or representative of him, as well as informing him of his disciplinary file, in addition to enabling him to appeal the disciplinary decision issued against him before the National Appeal Committee. Despite these guarantees, not limiting professional errors, as well as classifying them according to their gravity and determining the penalties required by each error may negatively affect the disciplinary system and its achievement of the desired goals of protecting the profession and professional. Keywords: Disciplinary responsibility, disciplinary decision, disciplinary error
Keywords: الكلمات المفتاحية: المسؤولية التأديبية، القرار التأديبي، الخطأ التأديبي